Pengembangan Instrumen Asesmen Penilaian Kinerja Mata Pelajaran Praktik Lapangan pada Fase F di SMKN 2 Singaraja - Ni Putu Novi Darmini; Ni Ketut Widiartini; I Wayan Artanayasa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to develop a valid and reliable performance assessment instrument for the Industrial Work Practice (PKL) subject, especially in the Fashion Design Expertise Program, and to evaluate the quality of the instrument for Phase F students. The trial subjects of this study consisted of 14 educators of the Fashion Design Expertise Program and 72 Phase F students specializing in Fashion Design in Bali Province. The design of this study follows the ADDIE development model, with instrument development procedures including content validity testing with the Content Validity Ratio (CVR) index, item internal consistency with the product moment correlation coefficient, instrument reliability with the Cronbach's alpha formula, item discrimination test, and parameter estimation analysis of the PKL course performance instrument. The results of the study show that: (1) The CVR value of each item is 1.00; (2) The correlation index of each item exceeds the critical value in the r-table and the instrument reliability coefficients, respectively, which indicate high reliability; and (3) Based on the item discrimination index, there are 106 items in the very good category, 49 items in the good category, and 14 items in the bad category.